Female entrepreneurs in Singapore - Chia, Iris (2015)
The growing importance of entrepreneurship in Singapore and the increasingly prominent role of women in society highlights the potential contributions of women entrepreneurs towards the growth of the Singapore economy. This study thus looks at the female entrepreneur in Singapore. It begins with a literature review of the motivations, characteristics and problems faced by female entrepreneurs. An empirical research consisting of interviews and questionnaires was conducted in the same areas for the purpose of comparison. The comparison revealed similarities in the characteristics and problems faced by female entrepreneurs and her overseas counterparts as established in the literature. This comparison is supplemented by a study of female entrepreneurs in several Asian countries. In particular, factors such as economic conditions, availability of assistance schemes and the status of women in the various Asian countries were examined.In addition, a comparison between male and female entrepreneurs in Singapore was also undertaken and this revealed several differences. For example, male and female entrepreneurs came from different educational backgrounds and female entrepreneurs experienced the lack of technical knowledge as a barrier at operational level, a problem that male entrepreneurs do not seem to encounter. As expected, the personal problems confronting female entrepreneurs also differ. For women, personal problems usually centred around the difficulty in handling both a business and a family. In response to the problems faced by female entrepreneurs, this study also attempts to identify possible solutions and recommendations which not only help alleviate the problems that female entrepreneurs currently face but also help to further promote entrepreneurship among women. Despite the burgeoning interest in entrepreneurship in Singapore, there is as yet little research conducted on women entrepreneurs in Singapore. It is hoped that perhaps this study can serve as a catalyst to spark-off more research in this area.